A review on the seroprevalence of Coxiella burnetii in farm ruminants in various countries - Pexara, Andreana; Solomakos, Nikolaos; Govaris, Alexander (Veterinaria Italiana, 2019)
Q fever is a zoonosis caused by Coxiella burnetii, an obligate intracellular gram‑negative bacterium. Infection by C. burnetii has been demonstrated in many animal species, but ruminants are the major reservoirs and the main sources of human infection. In ruminants, C. burnetii infection is often asymptomatic, but it has been also associated with infertility and abortions. In humans, Q fever was considered predominately an occupational hazard due to close contact with infected ruminants by means of their contaminated birth products, urine, feces or milk. Q fever has recently gained renewed attention after the large outbreak in the Netherlands in 2007‑2009, indicating its importance as an emerging public health threat. The seroprevalence of C. burnetii in ruminants is commonly detected by various tests but no official standard technique is still available. According to surveys conducted in many countries of the five continents, a relatively high proportion of farm ruminants are found seropositive to C. burnetii. The only country with an apparent zero prevalence is New Zealand. The seroprevalence in goats and sheep is usually higher than cattle.